Strategies for Improving Inventory Turnover at PT PK Manufacturing Indonesia - Mariyana, Mariyana; Karunia, R. Luki (Dinasti Publisher, 2025)
The objective of this study is to examine the factors influencing inventory turnover at PT PK Manufacturing Indonesia and to develop methods for improving inventory management efficiency. This research employs a qualitative approach, incorporating observations, interviews, and document analysis conducted at the research site, which includes the company’s warehouse and production facilities. The study aims to provide in-depth insights into the factors affecting inventory turnover and offer strategic recommendations for optimizing inventory management. Ultimately, this research will contribute to strategic management studies by presenting an effective approach to inventory management. The findings of this study are expected to benefit PT PK Manufacturing Indonesia and serve as a guideline for other manufacturing companies facing inventory turnover challenges.